Burden and Regional Disparities in the Firearm Mortality Profiles in Brazil: A Systematic Analysis of Findings From the Global Burden of Disease 2019 - Paula Protti, MD; Beatriz Remondes Sequeira, MD; Luiza Morais de Oliveira, MD; Francisco Winter dos Santos Figueiredo, MsC, PhD (Elsevier, 2024)
Introduction: Owing to legislative changes and regional disparities, knowledge of firearm death profile in Brazil is limited, creating a complex situation that requires data to improve the strategies to reduce the burden of this health problem. The aim of this study was to describe the burden of firearm injuries and regional disparities in Brazil, including the characterization of mortality profiles specifically in the year 2019. Method: The researchers extracted secondary data from the Institute of Health Metrics and Evaluation, from Global Burden of Disease study, including information on new cases and deaths caused by firearms. They also examined metrics such as incidence, mortality, years of life lost owing to disability, years of life living with disability, and years of life lost owing to premature death. Descriptive statistics (number of deaths and proportion) were performed. Results: The findings reveal that nearly 50,000 firearm-related deaths occurred in Brazil in 2019, corresponding to a rate of 21.6 deaths per 100,000 inhabitants. These deaths collectively contributed to around 3 million years of life lost when adjusted for disability. Notably, there are significant regional disparities, with the Northeast region of Brazil bearing a higher burden of firearm injuries. The study further differentiates mortality profiles on the basis of the type of firearm-related death. Young individuals and young adults experience a higher mortality rate due to homicides. On the other hand, individuals aged ≥70 years are more prone to firearm-related suicides. Conclusions: Firearm injuries in Brazil have distinct mortality profiles. Acknowledging these different profiles is crucial when devising effective public policies to address this issue.